Satisfaction Assessment System With Servqual Method At Betungan Urban Village Office - M. Afif Alfuadi; Sapri Sapri; Rizka Tri Alinse (Jurnal Media Computer Science, 2022)
The community satisfaction index (IKM) is a measure of the assessment given by the community to the government for the services that have been provided. This is stated in the regulation of the Minister of PAN-RB No. 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey for Public Administration Units. The community satisfaction index analysis should always be carried out periodically so that it can be seen that the community's satisfaction with the services provided, especially at Betungan Urban Village Office. But in reality, so far, the Urban Village Office does not have a benchmark that is used as a forum to determine community satisfaction with these services. The service satisfaction assessment system at the Betungan Urban Village Office was created using the PHP programming language and MySQL database. This satisfaction assessment system can be accessed online via the link http://afif.vad.my.id, so that it can make it easier for the public to provide service satisfaction assessments. In helping the analysis of the service satisfaction assessment, this application has applied the Servqual Method where the assessment is divided into 2 parts, namely perceptions and expectations. In addition to this satisfaction assessment system, there are 2 application interfaces, namely administrators and people who have different functions. Based on the tests that have been carried out, the results show that the functionality of the application runs as expected